THE EFFECT OF WORK STRESS ON THE PHYSICAL AND MENTAL HEALTH OF HEALTH WORKERS IN HOSPITALS - Safrina Ramadhani (INJOSEDU: International Journal of Social and Education, 2025)
Work stress is the main challenge faced by health workers in hospitals due to the high workload, demands for professionalism, and emotional pressure in treating patients. This research aims to analyze the influence of work stress on the physical and mental health of health workers through a literature review from various academic sources in the last 5- 10 years. The method used is a systematic literature review by examining scientific journals, books and research reports that discuss work stress among health workers. The results of the study show that work stress has a negative impact on the physical health of health workers, including chronic fatigue, sleep disorders, increased risk of cardiovascular disease, digestive disorders, and a decrease in the immune system. Meanwhile, the impact on mental health includes burnout, anxiety, depression, and sleep disorders which can reduce the quality of life and performance of health workers. Several factors such as high workloads, lack of social support, and imbalance between work and personal life exacerbate the impact of work stress. On the other hand, social support, good coping strategies, and supportive organizational policies can weaken the negative impact. Thus, a comprehensive strategy is needed to manage the work stress of health workers, both through institutional policies and individual approaches, in order to maintain their well-being and ensure optimal health services for patients.